REIMAGINING CHARACTER EDUCATION: INTEGRATING DIGITAL VALUES LEARNING IN ELEMENTARY SCHOOLS - Sheik Mohamed S.H; Sam Hermansyah (CV. Fahr Publishing, 2025)
This study aims to explore the integration of digital tools in values education to support character development among elementary school students. In response to the increasing demand for 21st-century moral competencies, this research conducts a systematic literature review focusing on strategies, challenges, and innovations in digital-based character education. Using qualitative content analysis of 22 peer-reviewed articles published between 2020 and 2025, the study identifies recurring patterns and contextual differences in the implementation of values learning across various countries. The findings highlight that approaches such as digital storytelling, gamified moral tasks, and project-based learning significantly foster student engagement, empathy, and ethical reasoning. However, key challenges remain, including inadequate teacher training, culturally irrelevant content, and limited infrastructure. The novelty of this research lies in its ecosystemic perspective, proposing a holistic framework that links pedagogy, technology, school culture, and local wisdom into one cohesive character education model. Unlike previous studies that isolate digital literacy from moral development, this research emphasizes participatory learning and student co-creation of values-based digital content. The study also introduces the concept of “contextual moral engagement,” where values are integrated into students’ daily lives through culturally grounded digital practices. In conclusion, digital integration in values education should move beyond tool-based interventions toward holistic, culture-sensitive, and participatory frameworks that empower students as moral agents in the digital age.